Mathematical Modelling of Gene Regulatory Networks - Al-shykhly, Ruaa Rifaat; Hameed, Lamyaa Mohammed Ali (Journal of Economics and Administrative Sciences, 2021)
This research includes the use of an artificial intelligence algorithm, which is one of the algorithms of biological systems which is the algorithm of genetic regulatory networks (GRNs), which is a dynamic system for a group of variables representing space within time. To construct this biological system, we use (ODEs) and to analyze the stationarity of the model we use Euler's method. And through the factors that affect the process of gene expression in terms of inhibition and activation of the transcription process on DNA, we will use TF transcription factors. The current research aims to use the latest methods of the artificial intelligence algorithm. To apply Gene Regulation Networks (GRNs), we used a program (MATLAB2020), which provides facilitation to the most important biological concepts for building this biological interaction